The Relationship between Social Interaction and Language Attitudes of Multiethnic High School Students in West Kalimantan - Elva Sulastriana; Yeni Rizal; Uray Herlina; Melina Lestari (AL-ISHLAH: Jurnal Pendidikan, 2024)
Language is an important symbol of social identity in multicultural societies. Language plays a very important role in individuals expressing themselves in their own culture or in other people's cultures. A problem among teenagers today is that the use of non-standard language varieties can sometimes have hidden prestige in society's speech. In multicultural societies, language has a very important role for individuals to express themselves in their own culture or in other people's cultures. The phenomenon that occurs is the background problem in this research, which examines whether there is a relationship between social interaction and language attitudes in multiethnic teenagers in Pontianak. The sample for this research was teenagers from six ethnic minorities in Pontianak: Malay, Dayak, Chinese, Madurese, Javanese, and Bugis. The research data was processed using non-parametric statistics with Spearman rank correlation. The results of the research show that, in general, there is a relationship between social interaction and language attitudes in multiethnic teenagers, but if we look at each ethnicity, the relationship between social interaction and language attitudes only occurs in the five ethnicities that Malay, Dayak, Chinese, Madurese, and Javanese ethnicities only, and these results apply to groups of male adolescents of all ethnicities. Even though the existing correlation results only show very weak correlation strength. Apart from that, for the Bugis ethnic group, there is no correlation between social interaction and language attitudes. This also occurs in multiethnic groups of female adolescents.